1992
DOI: 10.1016/0003-9969(92)90017-3
|View full text |Cite
|
Sign up to set email alerts
|

Amylase mRNA synthesis and ageing in rat parotid glands following isoproterenol-stimulated secretion

Abstract: In the parotid, as well as in other exocrine glands, secretory protein synthesis declines with age. However, whether this decline in the steady-state rate of protein synthesis reflects the reduced digestive activity of the animal or actual cellular alterations that affect synthesis is unknown. Here the ability to synthesize amylase and its mRNA during the period of enhanced protein synthesis following secretion induced by isoproterenol was compared in acinar cells of 2-and 24-month-old rats. In unstimulated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…In Figure 4, the rise in seric AMS activity (principally of salivary and pancreatic origin) between day 11 and day 40 after administration of saline, in group N, may be related to fluctuations in the rates of synthesis and secretion of the secretory glands. Such fluctuations have been attributed to aging of the animals [33–36]. The fall in AMS serum activity (Figure 4) corroborates the data of Barneo et al [3], who observed the same in diabetic animals and proposed a correlation with the severe insulin debt found in diabetes type 1, since this fall was not seen in type 2 cases [3].…”
Section: Discussionsupporting
confidence: 85%
“…In Figure 4, the rise in seric AMS activity (principally of salivary and pancreatic origin) between day 11 and day 40 after administration of saline, in group N, may be related to fluctuations in the rates of synthesis and secretion of the secretory glands. Such fluctuations have been attributed to aging of the animals [33–36]. The fall in AMS serum activity (Figure 4) corroborates the data of Barneo et al [3], who observed the same in diabetic animals and proposed a correlation with the severe insulin debt found in diabetes type 1, since this fall was not seen in type 2 cases [3].…”
Section: Discussionsupporting
confidence: 85%
“…This enzyme with predicted lysosomal localization, catalyzes the cleavage of alpha-1,4-glucosidic linkages between glucose molecules in starch, and thus plays an important role in starch digestion. It has been shown for parotid and other exocrine glands that synthesis of secretory proteins, especially alpha-amylases, declines with age, and the salivary function in general decreases [36]. This observation would explain significant decrease of alpha-amylase level in old mouse liver that we observe in our study.…”
Section: Identification Of Proteins Differentially Expressed In Peroxsupporting
confidence: 71%
“…In the present study we detected only a tendency for serum amylase activities to be lower in diabetic than normal rats throughout the experiment, such changes possibly being due to endocrine, exocrine and paracrine changes in the parenchyma of the pancreas [19,26,27]. In both normal groups the increased amylase activity observed during the experiment may have been related to fluctuations in the rates of amylase synthesis and its secretion by secretory glands, such fluctuations having been attributed to ageing of the animals [28-31]. The significant increase in amylase activity in the diabetic-treated group on day 33 relative to time zero does not necessarily indicate toxicity because there was no significant difference between the amylase activities of the diabetic-treated and diabetic-control groups on day 33, and it appears that the rise in amylase level in the diabetic-treated group on day 33 is probably due to a random effect.…”
Section: Discussionmentioning
confidence: 99%